(untitled) (Research, Society and Development, 2022)
Sepsis is considered a serious public health problem in the Intensive Care Unit (ICU), which, even with a great research effort in recent decades, remains a considerable and growing challenge to health care. The objective is to understand what are the factors associated with sepsis in patients hospitalized in the intensive care unit. This is an integrative literature review carried out through the VHL, LILACS, MEDLINE and PUBMED databases. 147 studies were found, after evaluation, 06 were selected to compose the final sample. The risk factors associated with sepsis in ICU patients are related to invasive procedures: mechanical ventilation, central vascular catheterization and catheterization, in addition to the long stay in the inpatient unit. These procedures are associated with the high number of deaths from sepsis in the intensive care unit, given that the risk of contamination and damage to the functioning of the organism is high. Studies have shown that the development of sepsis in the hospital environment is a factor that directly influences the impairment of patients’ quality of life, thus increasing the mortality rate.